Testosterone Propionate Exacerbates the Deficits of Nigrostriatal Dopaminergic System and Downregulates Nrf2 Expression in Reserpine-Treated Aged Male Rats - Cui, Rui; Kang, Yunxiao; Wang, Li; Li, Shuangcheng; Ji, Xiaoming; Yan, Wensheng; Zhang, Guoliang; Cui, Huixian; Shi, Geming (Frontiers in Aging Neuroscience, 2017)
Abstract There is a controversy over the effects of testosterone supplements on dopaminergic function. Both neuroprotective and toxic effects of testosterone supplements are reported. The status of oxidative stress seems to explain the neuroprotective or toxic properties of testosterone. To determine the efficacy of testosterone supplements in different status of oxidative stress, the present studies analyzed the dopamine (DA)-related behaviors and neurochemical indices, as well as markers of nigrostriatal dopaminergic (NSDA) system in reserpine-treated aged male rats followed by testosterone propionate (TP) supplements. The status of oxidative stress of experimental animals was evaluated by analyzing oxidative stress parameters and nuclear factor erythroid 2-related factor 2 (Nrf2)-antioxidant response element (ARE) signaling pathway in substantia nigra. Consistent with our previous studies, TP supplements to 21-month old aged male rats had the beneficial effects on NSDA system and DA-related behaviors and enhanced the antioxidative capabilities in substantia nigra. However, the beneficial effects of TP supplements on NSDA system and DA-related behaviors in aged male rats were reversed by reserpine pretreatment to them. Reserpine treatment induced the severe oxidative stress and reduced the expressions of Nrf2, heme oxygenase-1 (HO-1) and NAD(P)H:quinone oxidoreductase-1 (NQO1) in the substantia nigra of aged male rats. The TP supplements to reserpine-pretreated aged male rats exacerbated the defects in NSDA system and DA-related behaviors, aggravated oxidative damages and downregulated the expression of Nrf2, HO-1 and NQO1 in the substantia nigra. These results suggested that the efficacy of TP supplements on impaired NSDA system was related to the status of oxidative stress in experimental rats.